BIOREMEDIATION EFFICIENCY OF Exiguobacterium Profundum AND Bacillus Thuringiensis IN THE REMEDIATION OF BITUMEN - Ugwuja, Amarachi N; Adegunloye, Deke V; Olalemi, Adewale O (FUDMA Journal of Sciences, 2025)
Industrial activities are major contributors to environmental pollution, particularly in soil and aquatic ecosystems. As petroleum remains a primary energy source, its by-products, such as bitumen, are prevalent environmental contaminants. This study investigates the bioremediation potential of Exiguobacterium profundum and Bacillus thuringiensis in degrading bitumen. These bacteria were isolated from bitumen-contaminated soil in Ondo State, Nigeria, and identified through standard biochemical and molecular techniques. After 30 days of incubation, both strains exhibited significant bitumen-degrading capabilities. GC-MS analysis revealed that E. profundum (PP278055) transformed n-alkanes (C3–C20) into fatty acids including hexadecanoic acid, oleic, octadecanoic acid, pentadecanoic acid, octanoic acids and octadecenal compounds. Similarly, B. thuringiensis (PP278059) degraded n-alkanes (C5–C19) into acetic, hexadecanoic acid, oleic acids, and octadecenal compounds. These transformations indicate effective hydrocarbon biodegradation. Quantitative analysis showed that E. profundum achieved a higher bitumen weight loss (36.2%) compared to B. thuringiensis (31.6%). These findings suggest that both bacterial strains, particularly E. profundum, hold promise for the bioremediation of bitumen-contaminated environments.